With the frogs - Greenburg, J. C. (Judith C.); Gerardi, Jan (New York Random House, 2008)
Andrew, his cousin Judy, and Thudd the robot, having been shrunk by a shrinking machine, encounter many terrifying creatures, including Mrs. Scuttle, as they try to reach the Atom Sucker before it explodes.
"A stepping stone book."